Вечорниці (Життя − кабаре) - Gordey, Gordon (My University, 2014)
Gordon Gordey documents his dance concepts and director’s vision, including performance photographs, for the creation of 15 contemporary original dance works in a collection titled Vechornytsi, Life is a Cabaret. These danceworks were created for The Ukrainian Shumka Dancers of Canada.
Vechornytsi (Life is a cabaret)
Keywords: Ukrainian Shumka Dancers; Ukrainian dance; folk dance; Canadian dance; Dave Ganert; contemporary Ukrainian dance; Brian Cherwick; Oleh Skrypka; Ukrainian pop music; Vasya Club; Mykola Skoryk; Alexis Kochan; George Gershwin; Summertime